2018
DOI: 10.1096/fj.201800907rr
|View full text |Cite
|
Sign up to set email alerts
|

Isocitrate dehydrogenase 1–mutated human gliomas depend on lactate and glutamate to alleviate metabolic stress

Abstract: Diffuse gliomas often carry point mutations in isocitrate dehydrogenase (IDH1mut), resulting in metabolic stress. Although IDHmut gliomas are difficult to culture in vitro, they thrive in the brain via diffuse infiltration, suggesting brain‐specific tumor–stroma interactions that can compensate for IDH‐1 deficits. To elucidate the metabolic adjustments in clinical IDHmut gliomas that contribute to their malignancy, we applied a recently developed method of targeted quantitative RNA next‐generation sequencing t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
83
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(91 citation statements)
references
References 63 publications
5
83
0
3
Order By: Relevance
“…The most dominant changes between IDH1 mut and IDH1 wt gliomas were observed in enzymes and transporter proteins related to aerobic glycolysis and glutaminolyses. These observations confirm the previous findings at the RNA level [10][11][12] and strengthen the theory that both glutamate and lactate are imported and converted into α-ketoglutarate in IDH1 mut gliomas, to decrease metabolic stress caused by the mutation. [10][11][12] The increased import of lactate in IDH1 mut glioma cells results in a lower intracellular pH of tumor cells.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…The most dominant changes between IDH1 mut and IDH1 wt gliomas were observed in enzymes and transporter proteins related to aerobic glycolysis and glutaminolyses. These observations confirm the previous findings at the RNA level [10][11][12] and strengthen the theory that both glutamate and lactate are imported and converted into α-ketoglutarate in IDH1 mut gliomas, to decrease metabolic stress caused by the mutation. [10][11][12] The increased import of lactate in IDH1 mut glioma cells results in a lower intracellular pH of tumor cells.…”
Section: Discussionsupporting
confidence: 91%
“…10 More recently, a relationship between the IDH1 mut and lactate and glutamate dependency in glioma has been proposed. 11,12 Based on targeted RNA sequencing of a large series of metabolic enzymes, it was shown that enzymes transporting glutamate and lactate into the cell and enzymes converting lactate and glutamate into α-ketoglutarate are upregulated in IDH1 mut gliomas. 11 It was suggested that IDH1 mut gliomas depend on lactate and glutamate as metabolic substrates to alleviate metabolic stress as a result of defective isocitrate processing.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Of interest, IDH mutations are recently reported to be involved in multi‐layered metabolic activities in gliomas. Diffuse glioma cells with IDH mutations are dependent on glutamate and lactate, possibly supplied by neurons and astrocytes, and the dependency on these metabolites could open the way to novel approaches for treating IDH ‐mutant gliomas . The altered metabolic landscape in IDH ‐mutant gliomas also affects phospholipid, energy, and oxidative stress pathways .…”
Section: Metabolic Reprogramming In Diffuse Gliomasmentioning
confidence: 99%